2019
DOI: 10.15244/pjoes/94053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surrounding Environment and Management System in Apple Orchards on the Occurrence of Ground Beetles

Abstract: The aim of the observations was to determine the species composition of the Carabidae occurring in apple orchards with integrated and organic pest management, and to determine the impact of the surrounding areas on the Carabidae fauna appearing in those orchards. A total of 367 individuals of the Carabidae, representing 17 species from 15 genera, were collected in apple orchards with different management systems and surroundings. In both years of research, Carabidae beetles were the most numerous in the ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…These results support the conclusions of other studies on the impact of field boundary vegetation on the presence of beneficial insects [2,3,23,24]. According to the authors, the surrounding vegetation seems to be crucial for predatory species, while Grez and Prado [3] suggested that coccinellids can be affected not only by the surrounding vegetation but also by plant patch shape.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results support the conclusions of other studies on the impact of field boundary vegetation on the presence of beneficial insects [2,3,23,24]. According to the authors, the surrounding vegetation seems to be crucial for predatory species, while Grez and Prado [3] suggested that coccinellids can be affected not only by the surrounding vegetation but also by plant patch shape.…”
Section: Discussionsupporting
confidence: 88%
“…It should be emphasized that in the case of coccinellids, the impact of the vegetation surrounding the orchards on the presence of ladybugs in the orchard was smaller than in the case of other beneficial insects fe. syrphids or carabids [18,23,24]. Moreover, orchard surroundings also had an influence on the number and species richness of the Coccinellidae.…”
Section: Discussionmentioning
confidence: 99%
“…Although, in many cases, we failed to identify correlations between the syrphids occurring in the apple surroundings and those present in aphid colonies, based on current and previous researches [10,63], it can be concluded that even small clusters of flowering plants in the margins increase the abundance of beneficial insects within an orchard. The presence of trees and shrubs with herbaceous vegetation creates a suitable place for the development of the hoverflies (shelter and food), increasing their biodiversity.…”
Section: Discussionmentioning
confidence: 74%
“…This work tends to underline the different but complementary levers and the fact that no one mitigation measure can completely neutralize the unintended effects of PPPs. The importance of more global landscape-level characteristics, not only in transfers but also in organism vulnerability and the capacity of ecosystems to recover from PPPs (e.g., presence of refuge areas or diversification of vegetation around and within cultivated plots) is also clearly demonstrated in the literature (e.g., Lee et al 2001;Wojciechowicz-Zytko and Wilk 2019;Geldenhuys et al 2021;Klaus et al 2021).…”
Section: Levers For Action To Limit Ppp-driven Pollution and Effects ...mentioning
confidence: 98%